Integrated Control of Nonlinear Vehicle Stability - Jie Tian; Yaqin Wang; Ning Chen (Institute of Advanced Engineering and Science, 2013)
A novel vehicle stability control method integrated direct yaw moment control (DYC) with active front steering (AFS) is presented in this paper. By the phase plane of sideslip angle and sideslip angular velocity, vehicle stable region is determined. When the vehicle is outside the stable region, DYC controller is firstly used to produce proper direct yaw moment, which can make the vehicle back to the stable region. Then AFS controller of sliding mode variable structure is constructed and used to control the front steering angle of the actual vehicle, so that the sideslip angle and yaw rate of the actual vehicle model can track those of the reference vehicle model. Computer simulations are carried out on a 2-DOF nonlinear vehicle model to investigate the effectiveness of the proposed method. And the simulation results show that the influence of the proposed method on enhancing vehicle stability is significant. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2609